Testate amoebae (Arcellinida and Euglyphida) vs. Ericoid mycorrhizal and DSE fungi: a possible novel interaction in the mycorrhizosphere of ericaceous plants? - Vohník, M; Burdíková, Z; Albrechtová, J; Vosátka, M (Microbial ecology, 2009)
Common occurrence of testate amoebae (TA) in the rhizosphere of mycorrhizal plants indicates existence of yet undocumented ecological interactions, involving three distinct groups of organisms: soil protists, mycorrhizal fungi, and their host plants. This tripartite relationship was to date investigated only to a limited extent, despite its probable importance for processes taking place in the mycorrhizosphere. In this study, we (1) explored spectra of different TA genera naturally associated with the rhizoplane of three autochthonous European Rhododendron species, (2) screened natural fungal colonization of the TA shells occupying the rhizoplane of selected rhododendrons, and (3) carried out two in vitro experiments addressing the question whether TA shells may serve as a nutrient source for ericoid mycorrhizal fungi (ErMF) and dark septate endophytes (DSE). Our field observations indicated that TA regularly associated with the rhizoplane of all screened rhododendrons and that ErMF and/or DSE associated with their roots possibly exploited the TA shells as a nutrient source. We were unable to detect any major differences among the TA spectra from the rhizoplanes with respect to the three Rhododendron species. The spectra were dominated by Diplochlamys, Centropyxis, Cyclopyxis, Euglypha, Trinema, and Assulina. Positive, neutral, and negative associations were found for various TA genera x Rhododendron species combinations. The highest fungal colonization was observed in Centropyxidae and Trigonopyxidae, reaching up to 45% of the shells in the case of Trigonopyxis. In the in vitro experiments, both ErMF Rhizoscyphus ericae and DSE Phialocephala fortinii regularly colonized TA shells, utilizing them as a source of nutrients. We hypothesize a complex relationship between ErMF-DSE and TA. If corroborated, it would represent an interesting nutrient loop in the mycorrhizosphere of ericaceous plants.
Keywords: zvířata; mykorhiza; půda; Ericaceae; Plant Roots; Soil Microbiology; půdní mikrobiologie; Amoeba; Ecosystem; Animals; ekosystém; kořeny rostlin; Soil; Ascomycota; Rhododendron; Mycorrhizae